Laylī and Majnūn : Love, Madness and Mystic Longing in Niẓāmī's Epic Romance - Seyed-Gohrab, Ali Asghar (Brill Book Archive Part 1, ISBN: 9789004472495., 2003)
This book is the first comprehensive analysis of Nezāmī's romance Laylī and Majnūn (1188). It examines key themes such as chastity, constancy and suffering through an analysis of the main characters. Majnūn's asceticism, kingship, love-madness, poetic genius, ill-fate, and love-death are treated in separate chapters. The patriarchal society in which Laylī lives, her anxieties and dilemmas, incarceration, secret love, imposed marriage and finally her death are discussed in detail. One chapter is devoted entirely to the different ways parents raise their children and the consequences. Finally, the book gives an analysis of Nezāmī's style, the narrative structure of the romance and the symbolism of time and setting.